2007
DOI: 10.1039/b708324f
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrol of intramolecular Diels–Alder reactions by an allylic diphenylcyclopropyl group

Abstract: Intramolecular Diels-Alder reactions of ester-linked 1,3,8-nonatrienes carrying a diphenylcyclopropyl substituent attached to C1 proceed with high levels of stereoselectivity. The stereochemical outcomes of these reactions are explained by reference to B3LYP/6-31G(d) transition structures. Experimentally, the diphenylcyclopropane rings remain intact through these IMDA reactions, notwithstanding their predicted extremely high degree of asynchronicity (the B3LYP-computed lengths in the IMDA transition structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Parenthetically, we draw attention to the extraordinarily long developing “bond” —exceeding 3.0 Å— between the diene and the thionoester‐bearing carbon atom in the intermolecular endo ‐ 12 TS (Scheme ). The degree of bond asynchronicity (>1 Å) in this TS is unusually high for a non‐Lewis acid catalyzed DA reaction 16. 41a The B3LYP/6‐31+G(d) wavefunction for endo ‐ 12 TS is stable with respect to all perturbations treated by the GAUSSIAN 03 program,46 including relaxation of the wavefunction from restricted to unrestricted, thereby indicating insignificant biradical character in the wavefunction.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Parenthetically, we draw attention to the extraordinarily long developing “bond” —exceeding 3.0 Å— between the diene and the thionoester‐bearing carbon atom in the intermolecular endo ‐ 12 TS (Scheme ). The degree of bond asynchronicity (>1 Å) in this TS is unusually high for a non‐Lewis acid catalyzed DA reaction 16. 41a The B3LYP/6‐31+G(d) wavefunction for endo ‐ 12 TS is stable with respect to all perturbations treated by the GAUSSIAN 03 program,46 including relaxation of the wavefunction from restricted to unrestricted, thereby indicating insignificant biradical character in the wavefunction.…”
Section: Resultsmentioning
confidence: 96%
“…Consequently, endo ‐ 12 TS represents a case of an extremely asynchronous but concerted DA reaction in which one of the developing bonds, at 3.0 Å in length, is barely a bond at all. Such a high degree of asynchronicity, while not uncommon in Lewis‐acid‐catalyzed DA reactions,47 is unusual for an uncatalyzed DA reaction 16…”
Section: Resultsmentioning
confidence: 99%
“…For example, donor/acceptor carbenes exhibit a singlet ground state in chlorinated solvent as demonstrated both experimentally and computationally. [3] This singlet carbene can be accessed via the photolysis of donor/acceptor diazoalkanes and utilized in carbene transfer reactions, as recently demonstrated (2, Scheme 1b). [9] Contrarily, the spin state of aryl/aryl carbenes is much more dependent on the nature of the electronic properties of the substituents of the aromatic ring.…”
Section: Introductionmentioning
confidence: 97%
“…[1] In this context, experimental and theoretical studies on the influence of electronic effects on the carbene spin state remains a central area of research in physical organic chemistry. [1][2][3][4][5][6][7][8] In particular, matrix-isolation, ultrafast spectroscopy, or latest developments in computational chemistry represent important state-of-the-art techniques to characterize short-lived carbene intermediates. [2][3][4][5][6][7][8] These studies demonstrated that the electronic properties of substituents significantly impact on the spin state of carbenes and their singlet-triplet splitting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation